Karakteristik Kimia, Viskositas, dan Sensori Yoghurt Instan Berbahan Labu Kuning dengan Variasi Konsentrasi Tepung Porang - Dita Mustikarini; Nurrahman Nurrahman; Agus Suyanto (Universitas Pattimura, 2025)
Pumpkin is a rich source of dietary fiber and provitamin A, particularly β-carotene, and has potential for development into functional food products such as instant yoghurt. However, a thickening agent is required to enhance the texture and stability of the product. Porang flour, which contains a high concentration of glucomannan, can function effectively as natural thickener, binder, and substitute for commonly used gelling agents such as agar and gelatin. The research aimed to improve the chemical quality, viscosity and sensory properties of pumpkin yoghurt powder with differebt concentration of porang flour. The experimental procedure involved preparing pumpkin juice, fermenting it into yoghurt with porang flour added at varying concentrations (0.1%, 0.2%, 0.3%, and 0.4%), followed by instantization using the foam-mat drying The resulting products were analyzed for pH, moisture content, antioxidant activity, viscosity, and sensory properties. The results showed that the addition of porang flour significantly influenced all evaluated parameters. Including viscosity, pH, moisture content, antioxidant activity and sensory characteristics. The formulation containing 0.3% porang flour demonstrated the most favorable combination of physicochemical and sensory properties, indicating its potential as the optimal concentration for producing high-quality instant pumpkin yoghurt powder.